Personal and Communal Assumptions to Determine Pragmatic Meanings of Phatic Functions - Kunjana Rahardi (Lingua Cultura, 2016)
This research was meant to describe the manifestations of phatic function in the education domain. The phatic function in the communication and interaction happening in the education domain could be accurately identified when the utterances were not separated from their determining pragmatic context. The context must not be limited only to contextual and social or societal perspectives, but must be defined as basic assumptions. The data of this research included various kinds of speech gathered naturally in education circles that contain phatic functions. Two methods of data gathering were employed in this study, namely listening and conversation methods. Recorded data was analyzed through the steps as follows (1) data were identified based on the discourse markers found (2) data were classified based on the phatic perception criteria; (3) data were interpreted based on the referenced theories; (4) data were described in the form of analysis result description. The research proves that phatic function in the form of small talks in the education domain cannot be separated from the context surrounding it.